Casca de arroz e esterco bovino para a multiplicação de minhocas e produção de mudas de alface, tomate e boca-deleão - Steffen, Gerusa Pauli Kist (2008)
The earthworms are organisms of the edaphic fauna with great capacity of transformation of organic residues with stabled composting. The potential of these organisms have the advantage in the earthworm-breeding, seeking the humus production as organic fertilizer, and earthworm´s biomass, as food for several animals. However, many organic residues are not often used, staying in conditions that cause damages to the atmosphere. The present work was accomplished with the following objectives: to evaluated the utilization of rice husk and catle manure in the Eisenia andrei Bouché (1972) reproduction and the production of lettuce, tomato and snapdragon seedlings in the vermicomposts studied. Firstly, the efficiency of 30 substrates constituted by cattle manure and different forms of rice husk was evaluated (natural, charred, crushed and treated chemically with alkalis) in the multiplication of E. andrei. The study was conducted in greenhouse and were evaluated the number of young and adult earthworms, the number of cocoons, the biomass and multiplication index. These data was obtained after 60 days of earthworms inoculation. The efficiency of the use of the compositions was evaluated obtained as substrate for seedling production of lettuce (Lactuca sativa L.) cultivar Regina produced in plastic containers throughout 30 days. Secondly, it was analyzed the efficiency of different proportions of natural rice husk, charred rice husk and cattle manure in the creation of E. andrei, as well as the use of the vermicomposts obtained in the seedling production of tomato (Lycopersicon esculentum Mill) and lettuce in styrofoam trays. Thirdly, the potential of the charred rice husk and humus was evaluated in the seedling production of snapdragon (Antirrhinium majus L.) cultivar Potomac Light Rose. The seedling was produced in plastic trays in greenhouse and the features appraised were height, phytomass and number of pair leaf, 42 days after the sowing. The inclusion of rice husk to the cattle manure favored the multiplication and the development of the E. andrei. The vermicomposts used as substrate in the seedling production of tomato and lettuce was satisfactory and better quality than the commercial substrate. The substrates charred rice husk and humus present potential for using commercially in the seedling production acceptable of snapdragon in the proportions of 80, 60, 50 and 40% of charred rice husk added to the humus.